Different types of interpolations for solving delay differential equations using explicit Runge-Kutta method / Fudziah Ismail, Aung San Lwin and Mohamed Suleiman - Ismail, Fudziah; Lwin, Aung San; Suleiman, Mohamed (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2005)
Delay differential equations (DDEs) with single and multiple delays are solved using embedded explicit Runge-Kutta method. The delay terms are approximated by using divided difference interpolation, Hermite interpolation and continuous extensions formula of the Runge-Kutta method itself. Numerical results based on the different types of interpolation are tabulated and compared.